Effects of friction-based fixed bearings on seismic performance of high-speed railway simply supported girder bridges and experimental validation. Issue 3 (February 2019) - Jiang, Lizhong; Cao, Shanshan; Wei, Biao
This study investigated the seismic performance of simply supported girder bridges with a span length of 32 m. Those bridges were a common part in China's high-speed railway system and used spherical bearings to connect girders and piers. First, a finite element model of the scaled bridge with a geometrical similarity ratio of 1:8 was established by OpenSees. Second, five seismic damage states of fixed bearings and piers were defined based on the deformation failure criterion. Finally, an incremental dynamic analysis and a pseudo-dynamic test were performed to evaluate the effects of friction-based fixed bearings on the seismic response and damage state of bearings and piers. Results show that the sliding of friction-based fixed bearings effectively restricts the force transmitting between piers and girders, and reduces the seismic damage of piers. Those bearings with a small friction coefficient lead to a large relative displacement between piers and girders, while those bearings with a large friction coefficient cause a large seismic force exceeding the yield load of piers. Therefore, an appropriate friction coefficient of friction-based fixed bearing should be determined to achieve an optimal seismic performance of bridge according to the specific conditions of bridge and ground motion inputs.